2014
DOI: 10.1021/cb500343j
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Substrate and Metal Binding from the Crystal Structure of Cyanobacterial Aldehyde Deformylating Oxygenase with Substrate Bound

Abstract: The nonheme diiron enzyme cyanobacterial aldehyde deformylating oxygenase, cADO, catalyzes the highly unusual deformylation of aliphatic aldehydes to alkanes and formate. We have determined crystal structures for the enzyme with a long-chain water-soluble aldehyde and medium-chain carboxylic acid bound to the active site. These structures delineate a hydrophobic channel that connects the solvent with the deeply buried active site and reveal a mode of substrate binding that is different from previously determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 49 publications
0
40
1
Order By: Relevance
“…However, in these structures, ADO exhibits an occluded conformation, therefore, we were not able to identify the entry point for the aldehyde to access the active site of ADO based on our AAR-ADO complex structures. Previously reported crystal structures of PmADO showed that a T-shaped channel is present inside ADO, with an opening between helices 7 and 8 at the ADO surface, which was suggested to represent the entry point for aldehyde 20 . The helices 7 and 8 of ADO are at the AAR-ADO interface and helix 7 is essential for the complex formation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in these structures, ADO exhibits an occluded conformation, therefore, we were not able to identify the entry point for the aldehyde to access the active site of ADO based on our AAR-ADO complex structures. Previously reported crystal structures of PmADO showed that a T-shaped channel is present inside ADO, with an opening between helices 7 and 8 at the ADO surface, which was suggested to represent the entry point for aldehyde 20 . The helices 7 and 8 of ADO are at the AAR-ADO interface and helix 7 is essential for the complex formation.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, structure-based engineering of the two enzymes is a practical way to optimize the efficiency of alkane synthesis. Several crystal structures of ADO from different species of cyanobacteria were previously solved, revealing that ADO adopts a ferritin-like eighthelix (henceforth named helix 1-8) architecture, with a di-iron center buried inside the molecule [19][20][21][22] . An occluded substrate binding cavity accessing the di-iron center was identified in these structures 19,21,22 .…”
mentioning
confidence: 99%
“…The di-iron center is contained within an antiparallel four-α-helix bundle, where two histidines and four carboxylates (aspartate or glutamate) supply the protein ligands to the metal ions [1, 811]. The C1-derived co-product of the cADO-catalyzed reaction is formate (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial multicomponent monooxygenases (BMMs), found in methanotrophs and Gammaproteobacteria that thrive on hydrocarbons, exemplify here the O 2 utilizers. Comprised with BMM are soluble methane monooxygenase (sMMO), soluble toluene monooxygenase (sTMO) and related varieties, as well as phenol hydroxylase (PH) and cyanobacterial enzymes that carry out deformylation of aldehydes . All these metalloproteins are virtually colorless when accurately purified.…”
Section: Introductionmentioning
confidence: 99%